Four centuries on from Bacon: progress in building health research systems to improve health systems? - Hanney, Stephen R (BioMed Central, 2014)
In 1627, Francis Bacon’s New Atlantis described a utopian society in which an embryonic research system contributed to meeting the needs of the society. In this editorial, we use some of the aspirations described in New Atlantis to provide a context within which to consider recent progress in building health research systems to improve health systems and population health. In particular, we reflect on efforts to build research capacity, link research to policy, identify the wider impacts made by the science, and generally build fully functioning research systems to address the needs identified. In 2014, Health Research Policy and Systems has continued to publish one-off papers and article collections covering a range of these issues in both high income countries and low- and middle-income countries. Analysis of these contributions, in the context of some earlier ones, is brought together to identify achievements, challenges and possible ways forward. We show how 2014 is likely to be a pivotal year in the development of ways to assess the impact of health research on policies, practice, health systems, population health, and economic benefits. We demonstrate how the increasing focus on health research systems will contribute to realising the hopes expressed in the World Health Report, 2013, namely that all nations would take a systematic approach to evaluating the outputs and applications resulting from their research investment.